2012
DOI: 10.1021/jp303914x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the O(3P) + CH4 → OH + CH3 Reaction Is Similar To That of a Triatomic Reaction

Abstract: The O((3)P) + CH(4) reaction has been investigated using the quasi-classical trajectory (QCT) method and an ab initio pseudotriatomic potential energy surface (PES). This has been mainly motivated by very recent experiments which support the reliability of the triatomic modeling even at high collision energy ( = 64 kcal mol(-1)). The QCT results agree rather well with the experiments (translational and angular distributions of products); i.e., the ab initio pseudotriatomic modeling "captures" the essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…With regard to the vibrational ground-state reaction, O( 3 P) + CH 4 (ν = 0), the experimental studies [1][2][3][4][5] have shown that this reaction leads to cold rotational and non-inverted vibrational distributions of the OH product, low vibrational excitation of the CH 3 co-product, and a backward scattering angular distribution. The theoretical studies [6][7][8][9][10][11][12][13][14] are consistent with the experimental finding, associated with a rebound mechanism with a narrow cone of acceptance and a collinear CH 3 -H -O transition state. Recently, we reported a series of theoretical QCT studies [12][13][14] based on a new potential energy surface (PES-2014) developed by our group, 12 which is a full-dimensional analytical surface fitted exclusively to high-level ab initio calculations.…”
Section: Introductionsupporting
confidence: 86%
“…With regard to the vibrational ground-state reaction, O( 3 P) + CH 4 (ν = 0), the experimental studies [1][2][3][4][5] have shown that this reaction leads to cold rotational and non-inverted vibrational distributions of the OH product, low vibrational excitation of the CH 3 co-product, and a backward scattering angular distribution. The theoretical studies [6][7][8][9][10][11][12][13][14] are consistent with the experimental finding, associated with a rebound mechanism with a narrow cone of acceptance and a collinear CH 3 -H -O transition state. Recently, we reported a series of theoretical QCT studies [12][13][14] based on a new potential energy surface (PES-2014) developed by our group, 12 which is a full-dimensional analytical surface fitted exclusively to high-level ab initio calculations.…”
Section: Introductionsupporting
confidence: 86%
“…13 (3) The product angular distribution is predominantly backward-peaking. 17 In consistence with theoretical calculations, [3][4][5][6][7][8][9][10][11][12] all of these findings can be understood as a direct rebound mechanism with a preferentially collinear O-H-CH 3 transition state.…”
mentioning
confidence: 93%
“…Its thermal kinetics has been extensively studied both experimentally 2 and theoretically. [3][4][5][6][7][8][9][10][11][12] There are also a few experimental studies of the ground-state reaction dynamics, [13][14][15][16][17] from which the key observations can be summarized as follows. (1) The OH rotational distribution is relatively cold.…”
mentioning
confidence: 99%
“…The value of the ab initio pseudo-triatomic modeling has also been recognized for other analogous X + CH 4 reactions with PESs of very different shapes. 38 Although this model only accounts for two of the possible reaction channels for O( 1 D) + CH 4 , it should be emphasized that one of them (CH 3 + OH) corresponds to the dominant channel and the other one (CH 3 O + H) is also significant. 10,13 In addition, the (barrier-less) ground PES, which presents the deep CH 3 OH minimum along the MEP, is expected to be much more reactive than the excited PESs leading to products.…”
Section: Introductionmentioning
confidence: 99%